Region-specific alterations of AMPA receptor phosphorylation and signaling pathways in the pilocarpine model of epilepsy. (August 2015) - Lopes, Mark William; Lopes, Samantha Cristiane; Costa, Ana Paula; Gonçalves, Filipe Marques; Rieger, Débora Kurrle; Peres, Tanara Vieira; Eyng, Helena; Prediger, Rui Daniel; Diaz, Alexandre Paim; Nunes, Jean Costa; Walz, Roger; Leal, Rodrigo Bainy
Highlights: The pilocarpine model in rodents reproduces the main features of TLE in humans. Pilo causes changes of GluA1-Ser 845 phosphorylation and PKA activity in the DH. Pilo induces up-regulation of GFAP and down-regulation of EAAT2 expression in the DH. Pilo causes changes GluA1-Ser 831 phosphorylation and PKC activity in the VH. Pilo neurochemical alterations take place in specific hippocampal sub regions. Graphical Abstract: Abstract: Disturbances in glutamatergic transmission and signaling pathways have been associated with temporal lobe epilepsy (TLE) in humans. However, the profile of these alterations within specific regions of the hippocampus and cerebral cortex has not yet been examined. The pilocarpine model in rodents reproduces the main features of TLE in humans. The present study aims to characterize specific alterations of the glutamatergic transmission and signaling pathways in the dorsal (DH) and ventral hippocampus (VH) and temporal cortex (Ctx) of male adult Wistar rats 60 days after pilocarpine treatment (chronic period). The western blotting analyzes show a decrease of AMPA glutamate receptor subunit (GluA1)-Ser 845 phosphorylation; reduction of ERK1 and PKA activity; up-regulation of GFAP and down-regulation of the glutamate transporter EAAT2 expression in the DH. In contrast, in the VH it was observed a decrease of GluA1-Ser 831 phosphorylation and JNKp54 and PKC activity. In the Ctx, only ERK1 phosphorylation/activity decreased. The level of GluA1-Ser 845 phosphorylation and PKA activity (DH) and the level of GluA1-Ser 831 phosphorylation and PKC activity (VH) appear to be correlated, respectively. These findings suggest a differential imbalance of the signaling pathways involved in the site-specific phosphorylation of AMPA receptor in the hippocampus. Furthermore, we suggest that dorsal hippocampus is probably more susceptible to the impairment of glutamate uptake and gliose, since only this area displayed a significant decrease of EAAT2 and increment of GFAP. Taken together, our study suggests that specific neurochemical alterations take place in hippocampal sub regions. This approach may be valuable for understanding the onset of seizures and the alterations of neuronal excitability in specific regions and may help to establish therapeutic targets for treatment of this neuropathology.